Beyond the Polis: Aristotle’s Beast - Martínez Rivera, Yuiza (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
In Aristotelian political philosophy, the biological definition of man as a “political animal” functions as the premise upon which the polis can be created. According to Aristotle, man is an animal characterized by rational and communicative abilities that drive him to build communities in pursuit of the “good life.” This definition of human nature presupposes the creation of the polis as the only space where man can fully develop his virtues and live a full and happy life. However, Aristotle’s conception of the polis, only grants political participation within it to individuals that fit this description. This restriction begets the question of who remains beyond the margins of the polis? Beyond the boundaries of this political space remain all those who make life possible in the polis: women, workers, and slaves. Further yet, beyond all economic and social networks, lies the concept that will be the purpose of this article, the “beast,” a human characterized by a lack of political disposition, both in developed instances (like the polis) and the more primitive ones (like a tribe or the home). Following Aristotle’s logic, bestial men are not useful members of the community because they do not fulfill the role of the political animal, as their actions are not guided by the pursuit of the common good. We will argue that as a result, the beast suffers a triple exclusion: political, because he is denied citizenship; social, since he is barred from participating in the community that supports the polis economically; and, biologically for he is excluded from the conceptual group of human.